2021
DOI: 10.1097/inf.0000000000003432
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Multisystem Inflammatory Syndrome in a 12-Year-old Male After COVID-19 mRNA Vaccine

Abstract: The pathophysiology of multisystem inflammatory syndrome (MIS) in children (MIS-C) is unknown. It occurs several weeks after COVID-19 infection or exposure; however, MIS is rarely reported after COVID-19 vaccination, and cases are mostly in adults. Herein, we present a 12-year-old male who had no prior COVID-19 infection or exposure and developed MIS-C after his first dose of COVID-19 mRNA vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“… 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2. 27 Two other reports described one person each for whom SARS-CoV-2 infection status was unclear; NAAT or antigen tests were negative but anti-nucleocapsid antibody testing was not done or not described. 29 , 30…”
Section: Discussionmentioning
confidence: 99%
“…After vaccination for COVID-19 commenced in the pediatric population, reports of MIS-C began. These reports included a 12-year-old male who had no prior SARS-CoV-2 infection or exposure but developed MIS-C after his first dose of the COVID-19 mRNA vaccine [ 59 ].…”
Section: Mis-a and Mis-c After Vaccinationmentioning
confidence: 99%
“…One child had diabetes mellitus as an underlying disease that may decrease vaccine effectiveness [9]. Similarly, MIS-C cases with vaccination history before diagnosis are rarely reported [10][11][12][13][14][15], leading to physician concerns regarding vaccine effectiveness or potential COVID-19 vaccine-associated MIS-C.…”
Section: Department Of Pediatric Infectious Diseases University Of He...mentioning
confidence: 99%